Analyzing spatial and distributional issues in specialized tourism economies: the case of Uruguay - Porto, Natalia (2019)
In this article, we analyses the sectorial and spatial distribution of wages in tourism employment, and its characteristics in Uruguay for the 2012-2016 period. We found that, in general, workers in the tourism sector are younger than in other economics sectors and have less years of formal education. Also, the sector exhibits a higher informality rates, lower wages and more weekly work hours. When then focused on the distribution of hourly wages, Southern Interior appears as the most equalitarian in terms of distribution of hourly wages, while Metropolitan Montevideo and Northern Interior exhibit, in general, higher concentration of wages. If we focus in economic activities within tourism, there are not overall regional patterns, although some features can be identified at state level.